Functional Yb-doped fiber with a bat-type refractive index distribution for beyond kilowatt all-fiber single-frequency laser amplification - Wei Li; Wei Liu; Yu Deng; Yisha Chen; Huan Yang; Qi Chen; Junjie Zheng; Hu Xiao; Zilun Chen; Zhiyong Pan; Pengfei Ma; Zefeng Wang; et al. (Light: Science & Applications)
Abstract High-power single-frequency fiber lasers with diffraction-limited spots are indispensable for a wide range of photonic applications and are particularly in advanced detection and sensing technologies. However, the simultaneous achievement of kilowatt-level output power and diffraction-limited beam quality has remained elusive in all reported single-frequency fiber laser systems to date, primarily due to limitations imposed by the stimulated Brillouin scattering (SBS) effect and transverse mode instability (TMI) effect. In this study, we demonstrate the design and manufacturing of an ultra-low numerical aperture (NA) functional Yb-doped fiber featuring a bat-type refractive index distribution, specifically engineered for single-frequency laser amplification. In the fabrication, we implemented multiple chelate gas filling and particle deposition iterations, leading to an active fiber with a bat-type refractive index distribution. The unique capabilities of this large mode area and high-order modes leakage fiber (HOMLF) were demonstrated by stably amplifying the single-frequency laser with more than one kilowatt output power and near single mode beam quality (Mx 2 = 1.10, Mx 2 = 1.18) for the first time. This fiber design advances the leap forward in single-frequency fiber lasers, which could contribute as a novel and efficient laser amplification technique for the next generation of gravitational wave detection systems.